Production and nutrition rates of piatã grass and hybrid sorghum at different cutting ages - doi: 10.4025/actascianimsci.v35i3.18016 - Andréia Da Cruz Quintino; Joadil Gonçalves de Abreu; Roberto Giolo de Almeida; Manuel Cláudio Motta Macedo; Luciano da Silva Cabral; Rosemary Laís Galati (Acta Scientiarum. Animal Sciences, 2013)
The influence of cutting age on production and nutritive value of piatã grass (Brachiariabrizantha cv. BRS Piatã) and hybrid sorghum (Sorghum spp. cv. BRS 801) under an integrated croplivestocksystem was evaluated. The trial was carried out at the Embrapa Beef Cattle (2027 S; 5437 W) inCampo Grande, Mato Grosso do Sul State, Brazil, between April and October 2009. Experimental designconsisted of randomized blocks with four replicates. Treatments were distributed across a split-plot design,which included three production systems (single piatã grass; single hybrid sorghum; mixed cultivation ofsorghum and piatã grass). Half-plots consisted of three forage ages at harvest (with 70, 90 and 110 days afterseeding). Variables included agronomical characteristics, productivity and nutrition value. Regardless of theevaluated systems, cutting age affected agronomical characteristics and in vitro digestibility of organic matter(IVDOM). Production was highest (4,048 kg ha-1) within the integrated system. Regardless of cutting age,monoculture sorghum had the highest crude protein level. Results showed that integrated sorghum andpiatã grasses were an asset for forage productivity. Forages had higher values in crude protein and in in vitrodigestibility of organic matter on the 70th day after seeding.